Green Tax dan Green Incentive Sebagai Instrumen Menuju Ekonomi Berkelanjutan di Indonesia - Putri Gantine Lestari; Kaca Dian Meila; Suryaningsi Suryaningsi (Jurnal Proaksi, 2025)
Main Purpose - The purpose of this study is to analyze how Green Tax and Green Incentive can enchance tax revenues and promote environmentally friendly businesses to achieve a sustainable economy. Method - The research metode used in this study Is a Scooping Review, by the Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scooping Review (PRISMA-ScR) guidelines. Main Findings - The main findings in this research that Green Tax and Green Incentive are Proven can be an effective instruments for environmental protection but also to increase revenue. Theory and Practical Implications - This Study emphasizes that Green Tax and Green Incentive Serve a dual function as instruments for addressing environmental externalities while simultaneously driving rurtainable economic growth. The implication is that government should reinforce green fiscal reforms through more effective tax rates, integrated incentives and revenue allocation to support energy transition and the achievement of SGD’s. Novelty - The Novelty of thiss study lies in its comprehensieve examination of the role of green tax and green incentive in simultaneously enhancing state revenue and fostering green techological innovation to achieve a sustainable economy in Indonesia. Keywords: Green Tax, Green Incentive, State Revenue, Green Technology, Sustainable Economy.